Knowledge and Perception of Public Towards Medico Legal Autopsy in Nepal - Subedi, Nuwadatta; Paudel, Ishwari Sharma; Kandel, Dipendra; Chudal, Akash (Journal of Lumbini Medical College, 2018)
Introduction: Autopsy is an important tool to determine the cause of death. This study was conducted with the objectives to assess the knowledge and perception of Nepalese people towards medico legal autopsy. Methods: It was a questionnaire based cross sectional study performed among the general public of Nepal. A standard pretested questionnaire was used to collect the responses on knowledge and perception of the people about medico legal autopsy. Independent samples t-test was used to compare the mean score of knowledge among the various groups. P value of < 0.05 was considered significant. Results: Mean age of the respondents was 29.06 years (SD = 10.50) and 72.31% were male (n = 188, N = 260). Mean score of knowledge was 6.65 (SD = 1.76) out of a total ten. The score was significantly higher (p = 0.02) among the respondents whose relatives had undergone an autopsy than those whose were not. It was comparable among the educated and uneducated groups. A total of 75.77% respondents (n = 197, N = 260) would not reject the autopsy of their relatives. Conclusion: People lack knowledge mostly in basic elements of medico legal autopsy. Most of the people showed positive perception towards autopsy and those who were negative, feared of disfigurement of the bodies after an autopsy. DOI: https://doi.org/10.22502/jlmc.v6i1.210